Pengaruh Pendidikan Pancasila dalam Membentuk Karakter Peserta Didik di Sekolah Dasar - Ikhsan Ikhsan (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This article provides students with an understanding of the important role of Pancasila education in forming the character of elementary school students who are intelligent, creative and have noble character. The problems currently occurring are a lack of understanding about right and wrong behavior and a lack of direction from the school regarding character education. This research uses Systematic Literature Review (SLR) or systematic literature review. This research focuses on the use of clear and defined scientific methods to identify, select, evaluate, and summarize the results of relevant studies. Therefore, Pancasila has an important role in shaping the character of students in elementary schools, so it is necessary to instill Pancasila values in students through education. Character education through Pancasila needs to be implemented in elementary schools in order to improve the quality of Indonesia's young generation in the future. Therefore, it is hoped that Pancasila education can shape the character of students in accordance with Pancasila values.